Disjointed war : military operations in Kosovo, 1999 - Nardulli, Bruce R. (Rand, 2002)
The 1999 military operation in Kosovo had several deficiencies in joint military operations. This study examines all aspects of the conflict, including its political and historical underpinnings, in an attempt to understand these deficiences and to recommend improvements.